2017
DOI: 10.1080/13880209.2017.1357736
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity-guided isolation and identification of anti-adipogenic compounds from Sanguisorba officinalis

Abstract: Context:Sanguisorba officinalis Linne (Rosaceae) is a medicinal plant used traditionally for the treatment of inflammatory and metabolic diseases in Korea, China, and Japan. In our previous study, a 50% ethanol extract inhibited fat accumulation in 3T3-L1 adipocytes.Objective: This study investigates bioassay-guided fractionation, isolation, and identification of anti-adipogenic bioactive compounds in S. officinalis.Materials and methods: The bioassay-guided fractionation was conducted using effective differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…A loss in the mitochondria membrane potential and up-regulation of adiponectin was observed as well (Hsu and Yen, 2007). Some polyphenols such as isorhamnetin-3-O-D-glucuronide and ellagic acid isolated from Sanguisorba officinalis Linne also possess antiadipogenic properties (Im et al, 2017). Flavonoid glycosides (astragalin, isoquercetin, rhamnocitrin 3-O-glucoside, and nicotiflorin), triterpenes (methyl hederagenin) and triterpene glycosides (hederin, echinocystic acid 3-O-arabinoside and cauloside B) had a regulatory role in adipocytes differentiation.…”
Section: In Vitro Studiesmentioning
confidence: 96%
“…A loss in the mitochondria membrane potential and up-regulation of adiponectin was observed as well (Hsu and Yen, 2007). Some polyphenols such as isorhamnetin-3-O-D-glucuronide and ellagic acid isolated from Sanguisorba officinalis Linne also possess antiadipogenic properties (Im et al, 2017). Flavonoid glycosides (astragalin, isoquercetin, rhamnocitrin 3-O-glucoside, and nicotiflorin), triterpenes (methyl hederagenin) and triterpene glycosides (hederin, echinocystic acid 3-O-arabinoside and cauloside B) had a regulatory role in adipocytes differentiation.…”
Section: In Vitro Studiesmentioning
confidence: 96%
“…The Plant List ( The Plant List, 2021 ), International Plant Name Index ( International Plant Name Index, 2021 ) and Kew Botanical Garden ( Kew Botanical Garden, 2021a ; Kew Botanical Garden, 2021b ) were used for obtaining the scientific names and information on the subspecies and cultivars. Studies have demonstrated that the crude extracts from plants belonging to genus Sanguisorba or the purified monomers isolated from the plants of this genus exhibit various pharmacological activities, including anti-inflammatory ( Su et al, 2018a ; Guo et al, 2019 ; Yasueda et al, 2020 ), anti-cancer ( Liu et al, 2016 ; Nam et al, 2017 ; Tan et al, 2019 ; Bai et al, 2020a ; Liao et al, 2020 ), anti-lipid peroxidation ( Zhang et al, 2012a ; Romojaro et al, 2013a ; Kim et al, 2018a ; Lenzi et al, 2019 ), anti-bacteria ( Su et al, 2019 ; Zhu et al, 2020a ), anti-diabetes ( Kuang et al, 2011 ; Son et al, 2015 ), hepatoprotective ( Stojiljković et al, 2019 ; Meng et al, 2020 ), and anti-obesity ( Jung et al, 2016 ; Im et al, 2017 ; Ji et al, 2018 ) properties, both in vitro and in vivo ( Figure1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Sanguisorba officinalis L ( Figure 1 ), a traditional Chinese medicine which has been used in China for nearly 1000 years, has wide pharmacological activities including hemostasis, antidiarrheal, antineoplastic and increasing leucocytes. 10 The Sanguisorba officinalis is only needed 5 mg to treat leukopenia. Our previous study has confirmed that the Ziyuglycoside I (ZgI) ( Figure 1 ) is the crucial component of the Sanguisorba officinalis , which has prominent activity to increase the leucocytes.…”
Section: Introductionmentioning
confidence: 99%